Single w/o microemulsion templating of CdS nanoparticles - Huang, N.M.; Kan, C.S.; Khiew, P.S.; Radiman, S. (2004)
We report the synthesis of monodispersed CdS nanoparticle with tunable size by controlling the reaction aging time in a single water in oil (w/o) microemulsion system. The w/o microemulsion system consists of nonionic surfactant poly (oxyethylene) 5 nonyl phenol ether (NP5), poly (oxyethylene) 10 nonyl phenol ether (NP10), cyclohexane and aqueous solution (cadmium salt and thioacetamide). Thioacetamide (TAA) has been utilized as a source for slow release of sulfur ions in the in situ synthesis of CdS. UV-Visible spectra shows obvious blue shift for the CdS nanoparticles as compared to the bulk material due to quantum size effect. CdS nanoparticle size depends on the reaction aging time where longer reaction aging time yields bigger particles. CdS nanoparticles growth behaviour as a function of reaction aging time in the microemulsion system was characterized by UV-Visible spectroscopy. The particle growth follows a power law with an exponential in the order of 0.17. Energy Filter Transmissions Electron Microscopy (EFTEM) reveals monodispersed CdS nanoparticles with standard deviation, Ï less than 8. Â© 2004 Kluwer Academic Publishers.